2009
DOI: 10.3329/bsmmuj.v1i1.3687
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6: A Sensitive Parameter for the Early Detection of Neonatal Sepsis

Abstract: <p><strong>Background: </strong>Neonatal sepsis is a major cause of neonatal mortality and morbidity throughout the world. Though blood culture is the gold standard and has higher sensitivity and specificity over the hematological value and cytokine, it is not available in our community health situation and also in most of health care facilities. It is also time consuming. Therefore hematological value and interleukin-6 can be evaluated for the early diagnosis of neonatal bacterial infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
4
9
0
Order By: Relevance
“…In sepsis group, early onset was observed more (65%) than that of late onset of sepsis (35%). This observation was constant with the findings of others Noor et al [15] Khaleda et al [16] in BSMMU. Among the infected newborns, male were predominant (57.5%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In sepsis group, early onset was observed more (65%) than that of late onset of sepsis (35%). This observation was constant with the findings of others Noor et al [15] Khaleda et al [16] in BSMMU. Among the infected newborns, male were predominant (57.5%).…”
Section: Discussionsupporting
confidence: 93%
“…Male has only one X chromosome, so he is immunologically less protected than the females. Predominance of male babies suffering from neonatal sepsis was found in other study [15][16][17].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Comparison of tests showed that there is a significant difference between IL6 levels in the three groups (p Z 0.001). 19 9 In the study of Buck et al, (1994), IL6 was more sensitive than CRP in diagnosis of neonatal sepsis at the time of admission (73% towards 58%). 22 Adib et al,…”
Section: Articles Related To the Assessment Of Il6 (8 Article)mentioning
confidence: 98%
“…8 So hematological parameters and interleukins may be helpful for early diagnosis of neonatal sepsis. 9 Many studies have tried to find valid initial reaction of cytokines for early diagnosis of neonatal sepsis. 10 Inflammatory process in sepsis is very complex in terms of biochemical.…”
Section: Introductionmentioning
confidence: 99%